2015
DOI: 10.1136/thoraxjnl-2014-206609
|View full text |Cite
|
Sign up to set email alerts
|

Microfibrillar-associated protein 4 modulates airway smooth muscle cell phenotype in experimental asthma

Abstract: MFAP4 promoted the development of asthmatic airway disease in vivo and pro-asthmatic functions of bronchial smooth muscle cells in vitro. Collectively, our results identify MFAP4 as a novel contributor to experimental asthma, acting through modulation of airway smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…We have recently generated MFAP4-deficient mice and shown that they exhibit attenuated airway smooth muscle responses when subjected to an allergic asthma model (64). We have further investigated the steady state phenotype of MFAP4 deficiency and observed that MFAP4-null mice develop a spontaneous loss of lung function with moderate emphysema-like airspace enlargement, which progresses with age (65).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently generated MFAP4-deficient mice and shown that they exhibit attenuated airway smooth muscle responses when subjected to an allergic asthma model (64). We have further investigated the steady state phenotype of MFAP4 deficiency and observed that MFAP4-null mice develop a spontaneous loss of lung function with moderate emphysema-like airspace enlargement, which progresses with age (65).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 MFAP4 has recently been shown to promote the development of asthma in vivo and display proasthmatic properties of bronchial smooth muscle cells in vitro and has been suggested to contribute to allergic asthma by promoting airway eosinophilia, airway hyperresponsiveness, and lung remodeling through regulation of ASM proliferation and eotaxin secretion in experimental studies. 11 The objectives of this study were to investigate if the serum level of MFAP4 (sMFAP4) is associated with (a) asthma and (b) allergic sensitization in adolescents and young adults, and (c) whether sMFAP4 at the time of asthma diagnosis is associated with persistent asthma.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 MFAP4 has been associated with remodeling-related disorders, including liver fibrosis, 14 pulmonary airspace enlargement, 15 and atherosclerosis. 16 Furthermore, we recently showed that MFAP4 promotes airway SMC proliferation in experimental asthma, 17 suggesting that similar effects could be relevant for VSMC biology under pathological conditions. Moreover, recent in silico analysis predicted that Mfap4 deficiency can result in abnormal vascular physiology.…”
mentioning
confidence: 99%